One money for Europe - Fratianni, Michele; Peeters, Theo, 1937- (London : Macmillan, 1978)
The book examines the case for economic and monetary union; the properties of an inflation- proofed parallel currency, called the Europa; the types of exchange rate arrangements which are compatible with the Europa and conducive to the early adoption of monetary union; the advantages of the Europa mechanism over a stabilization of existing national monies and the institutional problems.
"The signatories to the Manifesto on European monetary union published in The Economist of All Saints' Day 1975 met their critics and supporters in Leuven at the end of November 1977 ... the proceedings of the conference constitute this book."
Includes bibliographies and index.
usc 31/7/17
Loans
Keywords: Monetary unions; Money; Europe--European Economic Community countries